2021
DOI: 10.1002/ceat.202100110
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate‐Based CO2 Capture through Nano Dry Gels + Tetrahydrofuran – A Kinetic and Thermodynamic Study

Abstract: The synergic effects of four combinations of nano dry gels plus tetrahydrofuran (THF) on the CO 2 capture and hydrate phase equilibrium were investigated. It was found that the hydrate phase equilibrium condition was almost identical with the mixture of nano dry gel + THF and THF solution. The gas storage capacity and CO 2 uptake rate increased significantly by THF concentration increment up to 19.06 wt % in the dry gel structure compared to a similar THF solution. The hydrate induction time decreased at highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Compared with the TBAB, THF, and CP, the TBAB and Al 2 O 3 nanoparticle compound additives can increase the gas absorption of the CO 2 /H 2 hydrate formation by 43.62%, 230.56%, and 173.27%, respectively. Golkhou et al 140 studied the influence of four dry nanogels (i.e., a combination of silica nanoparticles and THF) on the formation characteristics of the CO 2 hydrate, and the data showed that the combination of the 10 wt % silica nanoparticles + 5.56 mol % THF was the most beneficial to hydrate formation. In addition, Bozorgian et al 141 compared the effects of alkyl polyglycoside (APG), Al 2 O 3 nanoparticles, and TBAC on the storage capacity of the CO 2 hydrate formation and found that the combination of the Al 2 O 3 nanoparticles and TBAC improved the gas storage capacity.…”
Section: Thas + Nanoparticlesmentioning
confidence: 99%
“…Compared with the TBAB, THF, and CP, the TBAB and Al 2 O 3 nanoparticle compound additives can increase the gas absorption of the CO 2 /H 2 hydrate formation by 43.62%, 230.56%, and 173.27%, respectively. Golkhou et al 140 studied the influence of four dry nanogels (i.e., a combination of silica nanoparticles and THF) on the formation characteristics of the CO 2 hydrate, and the data showed that the combination of the 10 wt % silica nanoparticles + 5.56 mol % THF was the most beneficial to hydrate formation. In addition, Bozorgian et al 141 compared the effects of alkyl polyglycoside (APG), Al 2 O 3 nanoparticles, and TBAC on the storage capacity of the CO 2 hydrate formation and found that the combination of the Al 2 O 3 nanoparticles and TBAC improved the gas storage capacity.…”
Section: Thas + Nanoparticlesmentioning
confidence: 99%